Prevalence and patterns of HIV drug resistance in patients with suspected virological failure in North-Western Tanzania. (23rd November 2021) - Henerico, Shimba; Mikasi, Sello Given; Kalluvya, Samuel Elias; Brauner, Jan M.; Abdul, Seif; Lyimo, Eric; Desderius, Bernard; Korn, Klaus; van Zyl, Gert; Jacobs, Graeme Brendon; Preiser, Wolfgang; Kasang, Christa
Abstract: Background: More than 15 million people in sub-Saharan Africa receive ART. Treatment failure is common, but the role of HIV drug resistance in treatment failure is largely unknown because drug resistance testing is not routinely done. This study determined the prevalence and patterns of HIV drug resistance in patients with suspected virological failure. Materials and methods: A single high viral load of >1000 viral RNA copies/mL of plasma at any point during ART was considered as suspected virological failure. HIV-1 RNA was extracted from plasma samples of these patients using the QIAamp Viral RNA kit. The protease and part of the RT regions of the HIV pol gene were characterized. Results: Viral load was determined in 317 patients; 64 (20.2%) had suspected virological failure. We successfully genotyped 56 samples; 48 (85.7%) had at least one major resistance-associated mutation (RAM). Common mutations in RT were M184V (75%), T215Y (41.1%), K103N (39.3%), M41L (32.1%), D67DN (30.3%), G190A (28.6%) and A98G (26.8%). No RAMs were detected in ART regimens based on a ritonavir-boosted PI. Conclusions: The Tanzanian national guidelines define 'virological failure' as two consecutive viral load measurement results, at 3 month intervals, above the WHO threshold (1000 copies/mL). Here, we show that a single viral load above the WHO threshold is associated with high rates of RAMs. This suggests that a single high viral load measurement could be used to predict virological failure and avoid delays in switching patients from first-line to higher genetic barrier second-line regimens.